Influence of pretreatment for deashing of empty fruit bunches on pyrolysis products - Nur Sheli Akma, Ramli; Khairuddin, Md. Isa (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.